Assessment of awareness level among dentist regarding COVID-19 dental practice in Jammu city: a cross-sectional study - Gupta, Ankita; Chhibber, Needhika; Lihala, Ratika; Vaid, Pulkit; Abrol, Tushar; Joshi, Astha (International Journal of Research in Medical Sciences, 2021)
Background: Dentistry being one of the most exposed professions to COVID-19 infection, it has become necessary to establish a clinical protocol that should be applied in the working environment, to prevent the spread of virus. Methods: This Cross-sectional study was carried out on 393 practicing dentist of Jammu city. A Structured questionnaire was sent via internet to all the participants. The questionnaire consisted of demographic data (6 questions) and questions evaluating awareness (15 questions) of Dentist during COVID-19 Pandemic. The total awareness score was calculated based on subject’s responses. Descriptive statistics, independent t- test and one- way ANNOVA was used for statistical analysis. Results: Mean age of the participants was 32±7.03 years. Out of 393 participants 329 (83.7%) exhibited high level of knowledge. Based on educational qualification, those dental practitioner with MDS exhibited more mean knowledge score than BDS practitioner (14.428±0.8091 versus 12.641±2.688, p=0.000) Conclusions: Most of the study subjects had adequate knowledge regarding COVID- 19 dental practices. However, all the study participants were keen to attend educational programs/webinars to further upgrade their knowledge regarding COVID-19 dental practices.